Nasionalisme Indonesia dalam Dialektika Lokalitas dan Nasionalitas di Maluku - Steve Gaspersz (LIPI Press, 2019)
This article is an anthropological and historical reflections about the concept of nationalism which takes place on the dialectical interpretation on local and national identities in Maluku context. The main idea is on the effort to discover historical nexus about nationalism interpretatively that often disappear behind the grand narrative discourses about separatism of RMS (Republic of South Maluku) revolt whenever discussing the place of Maluku on Indonesian political map. By using combined methods of social hermeneutics and political anthropology paradigms, the elaboration developed in this article is unfolding new narrative of nationalism that might not be seen simply through centralistic viewpoint but analyzing various socio-political and historical interpretations of small narratives as the center of perspectives that must be considered within the discourse of Indonesian nationalism.